AWIL XOJALIǴI TÁLIM BAǴDARI STUDENTLERINE INGLIS TILIN CLIL TEXNOLOGIYASI TIYKARINDA ÚYRETIW - Nuratdinova, J.S. (SCIENCE and SOCIETY, 2023)
This article discusses the benefits of using CLIL technology in developing the communication skills of young agricultural education students in presents classrooms.